Rockwell Hardness Testing of Pure Nickel Collimators for BNCT Application - Erasmus Prakasita; Yohanes Sardjono; Budi Setyahandana (Universitas Gadjah Mada, 2019)
In this study, Rockwell and Brinell hardness testing was used to examine material hardness. These methods were chosen because they are easy to carry out, relatively inexpensive, and almost all sizes and shapes can be tested, in which nickel hardness before and after centrifugal casting are identified and compared. These tests enable the determination of the hardness numbers of nickel collimators using for boron neutron capture therapy. The samples were five nickel plates with a dimension of 4.5 × 4.5 cm and five collimators. The collimators were cylindrical and made using centrifugal casting. The basic principle of the hardness test was to apply loading on the object being tested. The Rockwell test was used to assess the material's hardness from the difference of indentation depth, while the Brinell test was used to determine the hardness from the diameter of indentation. From the results of this test, the hardness number of nickel before centrifugal casting is 168.53 BHN or 86.13 HRB, while the hardness number after centrifugal casting is 115.68 BHN or 64.84 HRB. It can therefore be concluded that centrifugal casting decreased nickel hardness.